Ambidexterity as a dynamic capability: Resolving the innovator's dilemma - O’Reilly, Charles A.; Tushman, Michael L. (Research in organizational behavior, 2008)
How do organizations survive in the face of change? Underlying this question is a rich debate about whether organizations can adapt—and if so how. One perspective, organizational ecology, presents evidence suggesting that most organizations are largely inert and ultimately fail. A second perspective argues that some firms do learn and adapt to shifting environmental contexts. Recently, this latter view has coalesced around two themes. The first, based on research in strategy suggests that dynamic capabilities, the ability of a firm to reconfigure assets and existing capabilities, explains long-term competitive advantage. The second, based on organizational design, argues that ambidexterity, the ability of a firm to simultaneously explore and exploit, enables a firm to adapt over time. In this paper, we review and integrate these comparatively new research streams and identify a set of propositions that suggest how ambidexterity acts as a dynamic capability. We suggest that efficiency and innovation need not be strategic tradeoffs and highlight the substantive role of senior teams in building dynamic capabilities.